2023
DOI: 10.1097/js9.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HER2 on prognosis and benefit from adjuvant chemotherapy in stage II/III gastric cancer patients: a multicenter observational study

Abstract: Background: Human epidermal growth factor receptor 2 (HER2) is a well-developed therapeutic target in breast and gastric cancer (GC). However, the impact of HER2 on survival and benefit from fluorouracil-based adjuvant chemotherapy remains unclear in patients with GC. Materials and Methods: This multicenter cohort study involved 5622 consecutive stage II/III GC patients. HER2 expression was assessed prospectively via immunohistochemistry (IHC). The stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…involved 5622 consecutive stage II/III GC patients and observed that HER2 overexpression was independently associated with a lower 5‐year OS in stage II, but not in stage III GC. 43 These findings together revealed that the impacts of HER2 amplification and PD‐L1 expression on prognosis in patients with GC remains controversial and should be re‐considered under different circumstances (e.g., clinical, pathological stage, genomic, transcriptomic, and immune landscapes).…”
Section: Discussionmentioning
confidence: 96%
“…involved 5622 consecutive stage II/III GC patients and observed that HER2 overexpression was independently associated with a lower 5‐year OS in stage II, but not in stage III GC. 43 These findings together revealed that the impacts of HER2 amplification and PD‐L1 expression on prognosis in patients with GC remains controversial and should be re‐considered under different circumstances (e.g., clinical, pathological stage, genomic, transcriptomic, and immune landscapes).…”
Section: Discussionmentioning
confidence: 96%
“…According to previous studies, low levels of HER2 expression account for 40% to 60% of all GC patients[ 14 ]. In a study involving patients with stage III GC, Gao et al [ 15 ] reported that the prognosis of patients with an HER2 score of 1 or 2+ was significantly better than that of patients with an HER2 score of 0 or 3+. In addition, most previous studies focused on the relationship between HER2 and tumor cell growth and apoptosis; relatively few studies have been conducted on the role of HER2 with respect to the immune cycle of tumors and the role of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical information of the internal populations was drawn from the Xijing Hospital of Digestive Diseases Gastric Cancer Database (XJHDDGCD). 17 , 18 This database contains prospectively collected clinicopathologic data, biological specimens, and follow‐up information on patients who were admitted to Xijing Hospital. Tissue samples from gastric cancer patients eligible for inclusion can be randomly selected for this study.…”
Section: Methodsmentioning
confidence: 99%